HR Technology Trends 2024: A Glimpse into the Future of Workforce Management - Syah Noor, Firman; Ade Prahasta, Yongky (Escalate : Economics and Business Journal, 2024)
This research article examines the key trends in HR technology projected for 2024 and their implications for workforce management. With a focus on the integration of artificial intelligence, HR analytics, remote work technologies, HR automation, and employee experience platforms, the study highlights how these innovations can enhance operational efficiency and employee engagement. Through qualitative methodologies, including in-depth interviews with HR professionals and case studies, the research identifies both the opportunities and challenges associated with adopting new technologies. Key challenges include employee resistance to change, budget constraints, and the necessity for comprehensive training programs. The findings suggest that effective change management strategies are essential for organizations to successfully implement HR technologies and leverage their full potential. Ultimately, organizations that embrace these trends are likely to improve their competitive positioning and foster a more engaged and productive workforce in an increasingly digital landscape.